2023
DOI: 10.1007/s00192-023-05629-8
|View full text |Cite
|
Sign up to set email alerts
|

International Urogynecology consultation chapter 2 committee 3: the clinical evaluation of pelvic organ prolapse including investigations into associated morbidity/pelvic floor dysfunction

Heather Barbier,
Cassandra L. Carberry,
Päivi K. Karjalainen
et al.

Abstract: Introduction and hypothesis This manuscript from Chapter 2 of the International Urogynecology Consultation (IUC) on Pelvic Organ Prolapse (POP) reviews the literature involving the clinical evaluation of a patient with POP and associated bladder and bowel dysfunction. Methods An international group of 11 clinicians performed a search of the literature using pre-specified search MESH terms in PubMed and Embase databases (January 2000 to August 2020). Public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…Accurately predicting de novo SUI has proven to be a challenge. Although occult SUI (i.e., sign of SUI observed only during prolapse reduction) is used as a predictor, its diagnostic accuracy varies across studies [ 27 ], and one of the largest studies indicated only a slight improvement over chance [ 23 ]. Consequently, it is not a standard practice in Finland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurately predicting de novo SUI has proven to be a challenge. Although occult SUI (i.e., sign of SUI observed only during prolapse reduction) is used as a predictor, its diagnostic accuracy varies across studies [ 27 ], and one of the largest studies indicated only a slight improvement over chance [ 23 ]. Consequently, it is not a standard practice in Finland.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is not a standard practice in Finland. A risk calculator that incorporates stress test results and various patient characteristics [ 23 ] offers moderate performance at best, with an area under the curve or concordance index ranging from 0.50 to 0.69 in external validation studies [ 27 29 ]. Its limited accuracy is understandable, given the weak, non-existent, and even conflicting correlations between its factors and de novo SUI.…”
Section: Discussionmentioning
confidence: 99%